Imatinib targeted therapy for a patient with chronic eosinophilic leukemia - Prejzner, Witold; Szatkowski, Damian; Wasąg, Bartosz; Limon, Janusz; Hellmann, Andrzej (Contemporary Oncology/Współczesna Onkologia, 2005)
The hypereosinophilic syndrome is a heterogeneous group of diseases of unknown etiology and pathogenesis. The hypereosinophilic syndrome is diagnosed when eosinophilia of more than 1.5 G/l persisting for at least 6 months is observed and other diseases with eosinophilia such as allergic, parasitic or neoplastic diseases are excluded. According to the WHO, chronic eosinophilic leukemia could be distinguished from the hypereosinophilic syndrome when clonality of eosinophils is confirmed by a cytogenetic or molecular analysis. Chronic eosinophilic leukemia is a rare disease characterized by eosinophilia; during natural progression the symptoms of heart and lung failure may occur. The character of disease is clonal, caused by the mutation in imatinib sensitivity tyrosine kinase gene FIP1L1-PDGFRA. A case report of the patient diagnosed to have chronic eosinophilic leukemia resistant to busulphan, hydroxycarbamide, and encorton was shown. The artificial mitral valve was implanted because of the symptoms of circulatory failure and mitral regurgitation caused by the primary disease. The fusion FIP1L1-PDGFRA gene was found, which confirmed the diagnosis of chronic eosinophilic leukemia. The fast and permanent hematologic remission was established after beginning the treatment with imatinib (100 mg a day). As a maintenance therapy imatinib at a dose of 100 mg weekly was started and in a molecular test no FIP1L1-PDGFRA is observed.